AI dan Pemasaran Konten: Pendampingan bagi UMKM Di Desa Ampeldento Kecamatan Karangploso dalam Menciptakan Konten yang Menarik dan Efektif - Muhammad Tody Arsyianto; Budi Wahono (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Ampeldento Village, Karangploso Subdistrict, face significant challenges in creating attractive and effective marketing content in the digital era. Although artificial intelligence (AI) technology offers great potential to enhance marketing strategies, many MSME actors still do not fully understand how to utilize this technology optimally. This community service program aims to provide guidance and assistance to MSME practitioners in using AI to improve the quality and appeal of their marketing content.The methods used in this study include practical training and workshops focused on AI-based content creation, as well as data analysis to better understand the target market. This mentoring program is designed to enhance the skills of MSME actors in using digital tools and AI, and to help them formulate more effective marketing strategies.The results of the study show that MSME practitioners who participated in the mentoring program experienced a significant improvement in their content creation skills and their understanding of digital marketing strategies. In addition, there was an increase in the competitiveness of their products in the local market, with several participants reporting increased sales and positive customer interactions after applying the techniques taught.The implications of this study indicate that the application of AI in content marketing can serve as an effective solution for MSMEs to adapt to the increasingly complex demands of the digital market